Field notes and reading notes: studying with Barbara Kirshenblatt-Gimblett in the 1990s - Dias, N. (Museum Worlds, 2019)
In this article, I reflect on the experience of attending Barbara Kirshenblatt-Gimblett’s class Performance Studies Issues and Methods at New York University’s Tisch School of the Arts in the 1990s. Recalling the classes and field trips to events and sites in New York City, and the emphasis that she placed on reading texts and taking field notes, I consider the lessons I learned for performance studies, anthropology, and museums, and also for teaching, research, and scholarship in general. Why did this practice of taking notes from the field, from books in particular, and the note-taking practice in general, play such a central role in Kirshenblatt-Gimblett’s teaching? The steady and consistent focus both on theory and on the observation of social practices was a means of opening up new spaces for theoretical analysis or for a “performed theory,” to use Kirshenblatt-Gimblett’s term.